Informality, Class Structure, and Class Identity in Contemporary Argentina - Elbert, Rodolfo Gaston (2017)
The dynamics of peripheral capitalism in Latin America implies that a relevant proportion of the working class is employed or self-employed under informal employment arrangements. The neoliberal transformations of the 1990s deepened this feature of Latin American labor markets which was not reversed during the period of economic growth that followed the collapse of Neoliberalism. In this context, sociological debates have focused on the relationship between the formal and the informal fractions of the working class. Framed on these debates, this article analyzes biographical and family linkages that connect formal and informal workers in Argentina and the effect of these connections on the patterns of class self-identification of individuals. Data analysis provides evidence that the lived experience across the informality boundary makes formal workers more like informal workers in terms of class self-identification. I use survey data from the ?Encuesta Nacional de Estratificación y Movilidad Social en la Argentina? (ENES, CEDOP-UBA), applied in 2007 to a multistage probability sample of the Argentine population. The sample used in this analysis consists of individuals between 25 and 65 years old, who were part of the employed labor force at the time of the survey (N=2,035). The paper concludes with the implications of this evidence for debates around the class position of informal workers.